IDENTIFIKASI KARAKTERISTIK SAPI BALI SEBAGAI HEWAN KURBAN DI DESA GALUNG, KABUPATEN BARRU, SULAWESI SELATAN - Mubarak Z, Sultan; Akhsan, Fitriana (Journal Gallus Gallus, 2023)
This study aims to identify the vital statistics of Bali cattle as a requirement to become qurban livestock in Galung Village, Barru District, South Sulawesi. The location of the research was determined by purposive sampling with 12 Bali Bulls cattle. This study uses a quantitative descriptive analysis. The variables observed were the breed of cattle (color, dorsal line, horns) age, and vital statistics in the form of body weight, body length, chest girth, and gumba height. The results of this study are that Bali cattle at the research location in Galung Village have qualitative characteristics that are by Balinese cattle in general. The average body size value for Bali cattle for body weight is 258.5 kg; body length of 87.25 cm; chest girth of 144.08 cm; and gumba height of 109.95. All the Bali cattle in Galung Village are 2-3 years old and have no defects in the body so Bali cattle can meet the requirements as sacrificial (qurban) livestock. Keywords: Sacrifice, Bali Cattle, Body Size, Breed Cattle